Drive-by-bridge inspection for damage identification in a cable-stayed bridge: Numerical investigations. (15th November 2020) - Kildashti, K.; Makki Alamdari, M.; Kim, C.W.; Gao, W.; Samali, B.
Highlights: This paper extends the VBI framework to a large-scale bridge structure. Validation of the technique is demonstrated both numerically and experimentally. Successful detection, localization and assessment of damage is achieved. Significance of various parameters on effectiveness of the approach is investigated. Abstract: This paper presents one of the first attempts of indirect Bridge Health Monitoring (BHM) for cable damage identification in a cable-stayed bridge. The premise of the work is to identify the location and the severity of a sustained structural damage to the cables, measured solely by vibration response of a moving vehicle passing over the bridge. To this aim, new formulations of dynamic coupling between the vehicle and the bridge are developed, utilizing finite element (FE) approach and validated. Further, the proposed framework to obtain the Vehicle-Bridge Interaction (VBI) is extended to a large-scale cable-stayed bridge. Various damage cases, caused by a partial and incremental change in structural stiffness of cables, being representative of gradual sectional loss due to corrosion, are taken into account. A damage index based on the Empirical Mode Decomposition (EMD) scheme is presented, and through extensive numerical investigations, it is demonstrated that under certain vehicle parameters the vehicle vibration response not only is capable of identifying the suffered damage to the bridge, but also is able to identify the damage location, and further to assess its severity. The contributions of the work are fourfold: (1) Many of the existing studies only focus on the simplified models of the bridge based on a simply supported Euler–Bernoulli beam theory; however, this paper extends the VBI framework to a three-dimensional numerical model of a large-scale bridge structure, being rarely reported in the BHM context. (2) The validation of the technique is demonstrated through extensive numerical investigations on a statically indeterminate cable-stayed bridge. (3) Successful detection, localization and assessment of damage to the cables are obtained using realistic range of vehicle parameters without any bridge response measurements. (4) Through extensive parametric study, the significance of various parameters on the effectiveness of the proposed approach is carefully investigated and discussed.